Impact of European Union Funds on the Level of Cohesion of Regions in Poland - Rafał Czyzycki; Rafał Kloska; Elżbieta Ociepa-Kicinska; Piotr Szklarz (Communications of International Proceedings, 2020)
One of the main objectives of EU regional policy is to stimulate processes which enhance internal economic cohesion in individual regions. At the regional level, the purpose of cohesion may be perceived through the prism of the necessity to eliminate disparities between individual areas, i.e. districts (poviats), forming a given region, i.e. province (voivodeship). The aim of the study is to assess the impact of EU funds invested in individual Polish provinces on changing the level of diversity, and therefore the level of coherence of individual voivodeship in the area of social, economic, environmental and institutional and political governance. For this purpose were analyzed 208084 completed investment projects co-financing with Community funds amounted to PLN 433.5 billion, which were implemented in Poland in 2004-2018. The results of the conducted research clearly indicated areas in which there is a statistically significant relationship between the investments implemented with EU financial support and changes in the internal coherence of individual voivodships. This enables to issue recommendations regarding the way in which Community funds will be spent, which in the expected way affect the increase in internal cohesion of the regions.
Keywords: Economic Cohesion; Regional Policy; Economic Governance; Social Governance.